Analysis and identification of phytophagous nematodes in an irrigated area by central pivot (Research, Society and Development, 2021)
Nematodes can have varied effects on agriculture. Some species can cause damage to production, and other free-living species can be beneficial to pathosystems. Phytophagous species hinder the absorption of water and, consequently, nutrients, causing damage to the roots and subsequent fall in production. Knowing the soil, not only its chemical and physical composition, but also its macro and microbiota, are fundamental for crop productivity. Therefore, this work aimed to identify the nematode populations and their characteristics in the central pivot irrigation area, at the Instituto Federal Goiano Campus Ceres-GO. Sampling, identification, quantification and characterization were done during the cultivation periods of the area, with respect to their phenological phases. After the collection, the physical and chemical characteristics of the soil were analyzed, which showed to be extremely clayey, and with good fertility. In nematological analyzes, the presence of nematodes was not detected in the samples collected in the central pivot area.